Reproduction has different costs for immunity and parasitism in a wild mammal. (15th November 2019) - Albery, Gregory F.; Watt, Kathryn A.; Keith, Rosie; Morris, Sean; Morris, Alison; Kenyon, Fiona; Nussey, Daniel H.; Pemberton, Josephine M.
Abstract: Life history theory predicts that reproductive allocation draws resources away from immunity, resulting in increased parasitism. However, studies of reproductive trade‐offs rarely examine multiple measures of reproduction, immunity and parasitism. It is therefore unclear whether the immune costs of reproductive traits correlate with their resource costs, and whether increased parasitism emerges from weaker immunity. We examined these relationships in wild female red deer ( Cervus elaphus ) with variable reproductive allocation and longitudinal data on mucosal antibody levels and helminth parasitism. We noninvasively collected faecal samples, counting propagules of strongyle nematodes (order: Strongylida), the common liver fluke Fasciola hepatica and the red deer tissue nematode Elaphostrongylus cervi . We also quantified both total and anti‐strongyle mucosal IgA to measure general and specific immune allocation. Contrary to our predictions, we found that gestation was associated with decreased total IgA but with no increase in parasitism. Meanwhile, the considerable resource demand of lactation had no further immune cost but was associated with higher counts of strongyle nematodes and E. cervi . These contrasting costs arose despite a negative correlation between antibodies and strongyle count, which implied that IgA was indicative of protective immunity. Our findings suggest that processes other than classical resource allocation trade‐offs are involved in mediating observed relationships between reproduction, immunity and parasitism in wild mammals. In particular, reproduction–immunity trade‐offs may result from hormonal regulation or maternal antibody transfer, with parasitism increasing as a result of increased exposure arising from resource acquisition constraints. We advocate careful consideration of resource‐independent mechanistic links and measurement of both immunity and parasitism when investigating reproductive costs. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.